Flexible workpiece vibration suppression in milling process based on a new response metric - Xiaoming Zhang; Dong Zhang; Kok-Meng Lee; Han Ding (2015 IEEE International Conference on Advanced Intelligent Mechatronics (AIM), 2015)
Vibration suppression in milling thin-wall components (which are widely used aircraft wing structures, turbine blades and jet engine compressor) is essential for improving workpiece surface integrity. Dynamic deflections of flexible workpiece in milling are spatially distributed, and must be derived from the part vibration. To effectively control the dynamic deflections encountered in flexible workpiece milling, as well as avoid any potential interference between vibrated workpiece being machined and cutter, the paper presents a vibration suppression strategy employing machining parameter optimization for solving using time-FEA. Along with a distributed-parameter model that takes into account the workpiece dynamic deformation due to time-varying cutting forces, a new metric is defined for evaluating the vibration response of the workpiece during milling, upon which a minimax optimization is formulated as a sequential linear programming problem to minimize the vibration response metric subject to a set of specified constraints (imposed by process stability as well as chatter-free and minimum material removal rate requirements). An AL7075 blade with a relatively complex free-form surface was numerically simulated to illustrate the dynamics responses of the spatially distributed nodal points on a thin-wall workpiece, and demonstrate the application of the vibration response metric for optimizing the spindle speed subject to a specified set of constraints.